THE LENGTH OF BREASTFEEDING: THE ROLE OF PRENATAL EDUCATION AND LISTENING TO CLASSICAL MUSIC (Zdravstveni glasnik, 2024)
Introduction: The use of music in midwifery is a new research field and further studies and clear evidence are needed to make it a valuable element of midwifery care. The aim of the study was to prove the influence of education of pregnant women and listening to classical music on the frequency and length of breastfeeding at discharge from the maternity hospital and 6 weeks after delivery. ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎ ‎Subjects and methods: A prospective randomized controlled study was conducted in 2019. The sample consisted of pregnant women from the area of Hercegbosna County, 198 of them (N=198).Results: No significant difference was found in the frequency of exclusive breastfeeding and feeding with supplementation between the experimental and control groups at discharge (88.9% vs 92.2%). A significantly larger number of subjects in the experimental group were exclusively breastfed compared to the control group after 6 weeks (χ²=4.541; df=1; p-0.033).Conclusion: The results indicate that investments in the development of the competencies of pregnant women and the creation of conditions in maternity hospitals can significantly affect the duration of exclusive breastfeeding.